Positive and negative electrode slurry and preparation method thereof, positive and negative electrode material, battery and preparation method thereof
Through the improved preparation method of positive and negative electrode slurry and electrolyte components, the problem of poor thermal stability of ternary materials of lithium-ion batteries is solved, the stability and safety of the battery are improved, and the battery is safe and reliable under high temperature conditions.
Patent Information
- Application Number
- CN202411655216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The ternary materials of lithium-ion batteries have poor thermal stability and are difficult to pass the hot box test. The chemical reaction is violent, which makes it easy to generate flammable and explosive gases, affecting the safety performance of the battery.
The improved preparation method of positive and negative electrode slurry includes mixing and sonication in a vacuum environment to ensure the uniformity and adhesion of the material, and the use of LiFSI as the lithium salt to improve the thermal stability of the electrolyte.
It improves the stability and safety of the battery, ensures that the battery can pass the hot box test under high temperature conditions, reduces the generation of flammable and explosive gases, and improves the overall performance of the battery.
Smart Images

Figure CN119725351A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive and negative electrode slurry and a preparation method thereof, a positive and negative electrode material, a battery and a preparation method thereof. Background Art
[0002] With the development of the new energy industry, the requirements for battery safety performance are becoming increasingly higher, and batteries need to remain stable and reliable under various environmental conditions. Thermal Chamber Test is a key test method for evaluating the performance and safety of batteries under different temperature environments. By simulating various temperature conditions that batteries may encounter in actual use, the thermal chamber test can comprehensively evaluate the thermal stability, charge and discharge performance, cycle life and safety of batteries. This test is crucial to ensuring the reliability and safety of batteries under extreme temperature conditions.
[0003] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems. The positive active materials of lithium-ion batteries can include lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganese oxide (NMC), nickel cobalt aluminum oxide (NCA) and other types. Among them, ternary materials have high energy density and rate performance, and have good application prospects. However, ternary materials have poor thermal stability, especially high-nickel materials, which have a low decomposition temperature and are prone to decomposition when the temperature is too high. Secondly, the chemical reaction of ternary materials is very violent, and the reaction easily generates a lot of flammable and explosive gases. Due to the nature of ternary materials, ternary lithium batteries face some challenges in hot box testing and are difficult to pass safety performance tests such as hot box testing.
[0004] In summary, a method for improving battery stability is needed. Summary of the invention
[0005] The purpose of the present application is to provide a positive and negative electrode slurry and a preparation method thereof, a positive and negative electrode material, a battery and a preparation method thereof, which are beneficial to improving battery stability.
[0006] In order to solve the above problems, this application adopts the following technical solutions:
[0007] The first aspect of the present application discloses a method for preparing a positive electrode slurry or a negative electrode slurry, wherein the raw materials of the positive electrode slurry include a positive electrode active material, a conductive agent, a binder and a solvent, and the raw materials of the negative electrode slurry include a negative electrode active material, a conductive agent, a binder and a solvent. The raw materials of the positive electrode slurry and the raw materials of the negative electrode slurry include a liquid raw material and a solid raw material. The preparation method comprises: preparing a first mixed material: mixing the binder and the liquid raw material to obtain the first mixed material; preparing a second mixed material: mixing the solid raw materials to obtain the second mixed material; preparing a third mixed material: adding the first mixed material to the second mixed material, mixing uniformly, to obtain the third mixed material, namely the positive electrode slurry or the negative electrode slurry; wherein: at least one of the steps of preparing the first mixed material, preparing the second mixed material and preparing the third mixed material is carried out in a vacuum environment; at least one of the steps of preparing the first mixed material, preparing the second mixed material and preparing the third mixed material comprises mixing by ultrasonic treatment.
[0008] In one implementation of the present application, the vacuum degree of the vacuum environment is -5MPa to -1MPa.
[0009] In one implementation of the present application, at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material includes mixing by stirring and ultrasonic treatment.
[0010] In one implementation of the present application, the vacuum degree of the vacuum environment is -5MPa to -1MPa.
[0011] In one implementation of the present application, the frequency of the ultrasound is 10 kHz to 20 kHz.
[0012] In one implementation of the present application, in at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material, mixing is also performed by stirring, and the stirring rate is 2000rpm to 4000rpm, and the processing time is 0.5h to 3h.
[0013] In one implementation of the present application, in the step of preparing the third mixed material, the first mixed material is added to the second mixed material in multiple times.
[0014] The second aspect of the present application discloses a positive electrode slurry or a negative electrode slurry, wherein the positive electrode slurry or the negative electrode slurry is prepared by the preparation method disclosed in the first aspect of the present application.
[0015] The third aspect of the present application discloses a positive electrode material or a negative electrode material, wherein the positive electrode material or the negative electrode material comprises the positive electrode slurry or the negative electrode slurry disclosed in the second aspect of the present application.
[0016] The fourth aspect of the present application discloses a battery, which includes an electrolyte and the positive electrode material and the negative electrode material disclosed in the third aspect of the present application.
[0017] In one implementation of the present application, the electrolyte includes LiFSi in a content of 0.1% to 20%.
[0018] The fifth aspect of the present application discloses a method for preparing the battery described in the fourth aspect of the present application, comprising: preparing positive electrode materials and negative electrode materials: comprising preparing positive electrode slurry and negative electrode slurry, and coating to obtain the positive electrode material and the negative electrode material; preparing an electrolyte: the electrolyte comprises a lithium salt, a solvent and an additive; assembling the positive electrode material and the negative electrode material, and injecting the electrolyte to obtain the battery.
[0019] The beneficial effects of this application are:
[0020] The positive and negative electrode slurries of the present application have no agglomeration phenomenon, can be coated on the surface of the electrode piece relatively evenly, have good adhesion, and can improve the stability and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a surface morphology diagram of the positive electrode sheet of Example 1 of the present application.
[0022] Figure 2 This is a surface morphology diagram of the negative electrode sheet of Example 1 of the present application.
[0023] Figure 3 This is a surface morphology diagram of the positive electrode sheet of comparative example 1 of the present application.
[0024] Figure 4 This is a surface morphology diagram of the negative electrode sheet of comparative example 1 of the present application.
[0025] Figure 5 This is a surface morphology diagram of the positive electrode sheet of Comparative Example 2 of the present application.
[0026] Figure 6 This is a surface morphology diagram of the negative electrode sheet of comparative example 2 of the present application.
[0027] Figure 7 This is a surface morphology diagram of the positive electrode sheet of comparative example 3 of the present application.
[0028] Figure 8 This is a surface morphology diagram of the negative electrode sheet of comparative example 3 of the present application.
[0029] Fig. 9This is a surface morphology diagram of the positive electrode sheet of comparative example 4 of the present application.
[0030] Fig.10 This is a surface morphology diagram of the negative electrode sheet of comparative example 4 of the present application. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can effortlessly recognize that some of the features can be omitted in different situations, or can be replaced by other materials and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.
[0032] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0033] The serial numbers assigned to the components in this article, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning.
[0034] The positive electrode materials in lithium-ion batteries are divided into lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide (Li(Ni x Co y Mn 1-x-y )O2, lithium nickel cobalt manganese oxide is a multifunctional lithium-ion battery positive electrode active material. By adjusting the ratio of nickel, cobalt and manganese, the performance of the battery can be optimized to meet different application requirements. High nickel materials are suitable for applications with high energy density requirements). Among them, ternary materials have higher energy density and rate performance, but ternary materials have poor safety. This is mainly because ternary materials have poor thermal stability, especially high nickel materials, which have a low decomposition temperature. When the temperature exceeds 150°, the material will decompose. Secondly, the chemical reaction of ternary materials is very violent, and the reaction generates a lot of flammable and explosive gases. The material itself is also sensitive to moisture and is prone to side reactions. Finally, ternary materials are mainly for the goal of high energy density and high power batteries, in which the nickel content will be very high. Therefore, the current ternary lithium batteries are difficult to pass the hot box test.
[0035] In this application, by improving the coating of positive and negative electrodes and adding LiFSI to the electrolyte, the stability of the battery can be improved, especially for ternary lithium batteries with poor safety and difficult to pass the hot box test. By using our method, the battery can meet the standards and pass the hot box test. Through this application, a high-capacity, high-energy-density and high-safety nickel-cobalt-manganese-oxide lithium battery can be provided.
[0036] In view of this, the present application creatively proposes a positive and negative electrode slurry and a preparation method thereof, a positive and negative electrode material, a battery and a preparation method thereof, and has the following advantages:
[0037] (1) By adding the first mixed material (liquid) to the second mixed material (solid), the amount of the first mixed material added can be adjusted and distributed, and a suitable amount can achieve a better kneading effect.
[0038] (2) Adding the first mixed material to the second mixed material in several steps can stabilize the separated particles, prevent the particles from agglomerating again, and make the dispersion more uniform.
[0039] (3) Ultrasonic technology is added during the preparation process. The growth and rupture of bubbles generated by ultrasound can impact and disperse the agglomerates in the mixed material, and can also cause the material to flow at the macro level, making the mixing more uniform. Specifically, at the micro level, continuous ultrasonic vibration is used during the preparation process, so that a large number of bubbles are generated inside the material during the mixing process. The bubbles float upward and grow. When the bubble size reaches a certain critical value, the bubble growth rate increases rapidly, and then it ruptures instantly, forming a shock wave to disperse the agglomerates in the material; at the macro level, it manifests as a salt-containing environment during the material mixing process, which is conducive to the discharge of gas in the material and prevents the gas in the material from affecting the subsequent coating quality.
[0040] (5) Lithium salts include LiFSI. Compared with LiPF6, LiFSI has better ionic conductivity, thermal stability and electrochemical stability, and is easily soluble in water and various organic solvents with almost no side reactions. Its excellent thermal stability can help the battery pass the 135°C hot box test.
[0041] (6) There is no agglomeration of the positive and negative electrode slurries, and they adhere to the electrode sheets more evenly, with good adhesion, good thermal stability of the electrolyte, and good safety performance of the battery.
[0042] The present application is introduced below in conjunction with the accompanying drawings and specific implementation methods.
[0043] The present application firstly relates to a method for preparing positive electrode slurry or negative electrode slurry
[0044] In a specific embodiment, the raw materials of the positive electrode slurry include positive electrode active material, conductive agent, binder and solvent, and the raw materials of the negative electrode slurry include negative electrode active material, conductive agent, binder and solvent, wherein the raw materials include liquid raw materials and solid raw materials.
[0045] The positive electrode active material refers to lithium iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium cobalt oxide and other substances, and the negative electrode active material refers to graphite, silicon and other substances. The positive electrode active material and the negative electrode active material are usually solid materials.
[0046] In a specific embodiment, the positive electrode active material is a nickel cobalt manganese oxide lithium material.
[0047] In a specific embodiment, the particle size D50 of the lithium nickel cobalt manganese oxide material is 1 μm to 30 μm.
[0048] In a specific embodiment, the nickel content of the lithium nickel cobalt manganese oxide material is relatively high. In other words, in a specific embodiment of the present application, the lithium nickel cobalt manganese oxide material is a high-nickel material.
[0049] In a specific embodiment, the ratio of nickel element to the three elements of nickel, cobalt and lithium in the nickel cobalt manganese oxide material is 60% to 95%. For example, the ratio of nickel element to the three elements of nickel, cobalt and lithium in the nickel cobalt manganese oxide material is 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%.
[0050] In a specific embodiment, in the nickel-cobalt-lithium manganese oxide material, the ratio of nickel element to the three elements of nickel, cobalt and lithium is 80% to 95%.
[0051] In a specific embodiment, in the nickel cobalt lithium manganese oxide material, the ratio of nickel, cobalt and lithium is 9:0.5:0.5.
[0052] In the positive electrode slurry, the binder may be PVDF (polyvinylidene fluoride), the conductive agent may be CNT (carbon nanotube), SP (SuperP), and the solvent may be NMP (N-methylpyrrolidone). In the negative electrode slurry, the binder may be CMC (carboxymethyl cellulose), SBR (styrene-butadiene rubber), the conductive agent may be carbon nanotube (CNT), SP (SuperP), conductive glue, and the solvent may be NMP or water. Among them, the positive electrode active material, the negative electrode active material, and SP are usually solid raw materials, and NMP, water, CNT, and conductive glue are usually liquid raw materials.
[0053] In a specific embodiment, the preparation method of the positive electrode slurry or the negative electrode slurry includes:
[0054] (1) Preparing a first mixed material: mixing a binder and the liquid raw material to obtain a first mixed material.
[0055] (2) Preparing a second mixed material: mixing solid raw materials to obtain a second mixed material.
[0056] (3) Preparing a third mixed material: adding the first mixed material to the second mixed material, mixing them evenly, to obtain a third mixed material, namely, a positive electrode slurry or a negative electrode slurry.
[0057] The steps of preparing the first mixed material and preparing the second mixed material may be performed in any order.
[0058] In a specific embodiment, at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material is performed in a vacuum environment.
[0059] In a specific embodiment, the entire preparation process of the positive electrode slurry or the negative electrode slurry is carried out in a vacuum environment, that is, each step is carried out in a vacuum environment.
[0060] In a specific embodiment, the vacuum degree of the vacuum environment is -5MPa to 0MPa. For example, the vacuum degree of the vacuum environment may be -5MPa, -4MPa, -3MPa, -2MPa, -1MPa, -0.5MPa or 0MPa. Preferably, the vacuum degree of the vacuum environment is -5MPa to -1MPa. It should be noted that MPa is megapascals; the vacuum degree of the vacuum environment is -1MPa, which is approximately equal to minus 10 standard atmospheric pressures.
[0061] In a specific embodiment, in at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material, mixing is performed by ultrasonic treatment.
[0062] In a specific embodiment, ultrasonic treatment can be used for mixing during the entire preparation process of the positive electrode slurry or the negative electrode slurry, that is, ultrasonic treatment is used for mixing in each step.
[0063] In a specific embodiment, the frequency of ultrasound is 10kHz to 20kHz. For example, the frequency of ultrasound can be 10kHz, 11kHz, 12kHz, 13kHz, 14kHz, 15kHz, 16kHz, 17kHz, 18kHz, 19kHz or 20kHz.
[0064] In a specific embodiment, at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material further includes mixing by stirring.
[0065] In a specific embodiment, the stirring rate is 2000 rpm to 4000 rpm, and the processing time is 0.5 h to 3 h.
[0066] In a specific embodiment, an ultrasonic-double planetary agitator can be used to mix the materials, wherein the revolution speed of the ultrasonic-double planetary agitator is 20 rpm to 60 rpm, and the rotation speed is 2800 rpm to 3200 rpm.
[0067] In a specific embodiment, in the step of preparing the third mixed material, the first mixed material is added to the second mixed material in multiple times. For example, the first mixed material can be added twice, three times, or four times. It should be noted that adding the first mixed material to the second mixed material in batches can play a kneading role on the second mixed material. The high-speed rotating stirring paddle uses the friction between the surface inclined at a certain angle and the material to make the material move tangentially along the paddle surface. At the same time, due to the action of centrifugal force, the material is thrown to the inner wall of the mixing chamber and rises along the wall. When it rises to a certain height, it falls back to the center of the impeller due to gravity and is then thrown up again. This combination of rising motion and tangential motion actually puts the material in a continuous spiral motion state. Due to the high rotation speed of the paddle, the material movement speed is also very fast. The fast-moving particles collide and rub against each other, so that the particles or the agglomerates gathered together are broken, and the temperature of the material is also increased accordingly, which is conducive to the adsorption of various additives by the powder.
[0068] In a specific embodiment, the method for preparing the positive electrode slurry or the negative electrode slurry further includes: adding a binder to the third mixed material and adjusting the viscosity to obtain the positive electrode slurry or the negative electrode slurry.
[0069] In a specific embodiment, the viscosity of the positive electrode slurry or the negative electrode slurry is 2000 MPa·s to 4000 MPa·s.
[0070] In a specific embodiment, the method for preparing the positive electrode slurry or the negative electrode slurry further includes: screening the third mixed material after adjusting the viscosity and / or performing iron removal treatment.
[0071] In a specific embodiment, the screening process includes filtering with a 200-mesh screen.
[0072] In a specific embodiment, the iron removal process includes using an iron removal device to stir the slurry to remove magnetic substances in the slurry.
[0073] In a specific embodiment, the solid content of the first mixed material is 3% to 5%.
[0074] In a specific embodiment, the solid content of the positive electrode slurry or the negative electrode slurry is 55% to 80%, the viscosity is 2000 to 4000 MPa.s, and the fineness is ≤15 μm.
[0075] The present application also relates to a positive electrode slurry or a negative electrode slurry prepared by the above-mentioned method for preparing the positive electrode slurry or the negative electrode slurry.
[0076] The present application also relates to a positive electrode material or a negative electrode material, wherein the positive electrode material has the positive electrode slurry mentioned above, and the negative electrode material has the negative electrode slurry mentioned above.
[0077] In a specific embodiment, the particle size D50 of the positive electrode material is 1 μm to 5 μm, and the specific surface is 5 to 20 μm. 2 / g, density is 0.5~1g / cm 3 .
[0078] In a specific embodiment, the particle size D50 of the negative electrode material is 1 μm to 5 μm, and the specific surface is 5 to 20 μm. 2 / g, density is 0.5~1g / cm 3 .
[0079] The present application also relates to a battery, which comprises: the above-mentioned positive electrode material, the above-mentioned negative electrode material, and an electrolyte.
[0080] In a specific embodiment, the electrolyte includes: a lithium salt, a solvent and an additive.
[0081] In one embodiment, the lithium salt includes LiFSI (lithium bis(fluorosulfonyl)imide).
[0082] In one embodiment, the lithium salt includes LiPF6 (lithium hexafluorophosphate) and LiFSI (lithium bis(fluorosulfonyl)imide).
[0083] In a specific embodiment, the electrolyte includes 0.1% to 20% LiPF6 and / or 0.1% to 20% LiFSI. For example, the electrolyte may include 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20% LiPF6 and / or 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20% LiFSI. The contents are all expressed as mass fractions.
[0084] In a specific embodiment, the solvent of the electrolyte includes at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC).
[0085] In a specific embodiment, the additive of the electrolyte includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), diene sulfate (DTD), propylene sulfate (PS), and trivinylsilane (TVSi).
[0086] In a specific embodiment, in the electrolyte, DMC accounts for 45% to 55%, EMC accounts for 8% to 12%, PE accounts for 8% to 12%, VC accounts for 0.1% to 0.3%, TVSi accounts for 0.2% to 0.6%, FEC accounts for 8% to 16%, EC accounts for 2.5% to 3.1%, PC accounts for 12% to 16%, DTD accounts for 0.2% to 0.7%, and PS accounts for 1% to 1.4%. The contents are all expressed as mass fractions.
[0087] In a specific embodiment, the battery is a ternary lithium battery.
[0088] The present application also relates to a method for preparing a battery, comprising: preparing a positive electrode material and a negative electrode material, preparing an electrolyte, assembling the positive electrode material and the negative electrode material, and injecting the electrolyte to obtain a battery. The positive electrode material, the negative electrode material and the electrolyte can be referred to in the above content and will not be repeated here.
[0089] The present application is further described in detail below by specific examples. The following examples are only further described for the present application and should not be construed as limiting the present application. It should be noted that the reagents, test kits, instruments, etc. used in the examples are all commercially available, and the operating steps are carried out according to the instructions or the general operating steps in the art.
[0090] Embodiment 1:
[0091] (1) Preparation of positive electrode slurry:
[0092] 1) Prepare wet material:
[0093] PVDF was mixed with NMP and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 30 rpm for revolution, 2800 rpm for rotation, an ultrasonic frequency of 20 kHz, a time of 3 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material A.
[0094] CNT was added to material A and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 2800 rpm, an ultrasonic frequency of 10 kHz, a time of 0.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material B.
[0095] 2) Preparation of dry materials:
[0096] The nickel, cobalt and lithium manganese oxides were mixed and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 5 rpm, an ultrasonic frequency of 10 kHz, a time of 30 min, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material C.
[0097] SP was added to material C and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 40 rpm, an ultrasonic frequency of 20 kHz, a time of 0.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material D.
[0098] 3) Total mixing:
[0099] 70% and 30% of material B were added to material D in two portions, and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 1300 rpm, an ultrasonic frequency of 20 kHz, a time of 3.5 h, a temperature of 20-30°C, and a vacuum degree of -1 MPa to obtain material E.
[0100] Appropriate amount of NMP was added to material E to adjust the viscosity of material E to 2000-4000 MPa.s, thereby obtaining material F.
[0101] 4) Using a 200-mesh screen, material F was screened at a vacuum degree of -0.01 MPa to remove larger particles in the slurry, and an iron removal device was used to stir the slurry to remove magnetic substances in the slurry.
[0102] In this embodiment, by weight, it includes 0.55 parts of PVDF, 15.5 parts of NMP, 15 parts of CNT, 100 parts of lithium nickel cobalt manganese oxide (wherein the ratio of nickel, cobalt and lithium is 9:0.5:0.5), and 1 part of SP.
[0103] (2) Preparation of negative electrode slurry:
[0104] 1) Prepare wet material:
[0105] CMC and deionized water were mixed and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 2800 rpm, an ultrasonic frequency of 10 kHz, a time of 1.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material G.
[0106] Material G was mixed with CNT and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 60 rpm, 2800 rpm, an ultrasonic frequency of 20 kHz, a time of 0.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material H.
[0107] Material H was mixed with the conductive adhesive and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 3200 rpm, an ultrasonic frequency of 20 kHz, a time of 1 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material I.
[0108] 2) Preparation of dry materials:
[0109] Graphite was mixed with SP and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 10 rpm for revolution, 3200 rpm for rotation, an ultrasonic frequency of 20 kHz, a time of 3 h, a temperature of 20-30°C, and a vacuum degree of -1 MPa to obtain material J.
[0110] 3) Total mixing:
[0111] Material J was mixed with 20% of material I and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 300 rpm, an ultrasonic frequency of 20 kHz, a time of 1.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material K.
[0112] Material K was mixed with 55% of material I and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 20 rpm, 3000 rpm, an ultrasonic frequency of 10 kHz, a time of 1.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material L.
[0113] Material L was mixed with 25% of material I and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 2 rpm for revolution, 500 rpm for rotation, an ultrasonic frequency of 10 kHz, a time of 1.5 h, a temperature of 20-30° C., and a vacuum degree of -1 MPa to obtain material M.
[0114] Add appropriate amount of NMP and SBR to material M to adjust the viscosity of material M. The viscosity range is 2000-4000 MPa.s.
[0115] 4) Using a 200-mesh screen, the material M is screened at a vacuum degree of -0.01 MPa to remove larger particles in the slurry, and an iron removal device is used to stir the slurry to remove magnetic substances in the slurry.
[0116] In this embodiment, by weight, 0.45 parts of CMC, 82 parts of deionized water, 15 parts of CNT, 2 parts of conductive glue, 100 parts of graphite, 1 part of SP, and 1.2 parts of SBR are included.
[0117] (3) Preparation of electrolyte:
[0118] The electrolyte includes lithium salt, solvent and additives, wherein the lithium salt includes LiPF6 and LiFSI, the solvent includes DMC, EMC, EC, PC, and the additives include VC, PE, FEC, DTD, PS, TVSi.
[0119] Among them, in the electrolyte, by mass ratio, LiPF6 accounts for 3%, LiFSI accounts for 3.5%, DMC accounts for 50%, EMC accounts for 9%, EC accounts for 2.8%, PC accounts for 13.8%, VC accounts for 0.2%, PE accounts for 9%, FEC accounts for 12%, DTD accounts for 0.5%, PS accounts for 1.2%, and TVSi accounts for 0.4%.
[0120] (4) Battery preparation:
[0121] The positive electrode slurry is applied to the positive electrode sheet (aluminum foil), and the negative electrode slurry is applied to the negative electrode sheet (copper foil). The coating parameters are: surface density 17.3 mg / cm 2 , compacted density 1.6g / cm 3 , thickness 0.047mm. Then, the positive and negative electrode sheets and the electrolyte are wound into a cylindrical battery.
[0122] Comparative Example 1:
[0123] The LiSFI in the electrolyte was removed, and other conditions were the same as those in Example 1.
[0124] Comparative Example 2:
[0125] The ultrasound during the preparation of the positive and negative electrode slurries was removed, and other conditions were the same as in Example 1.
[0126] Comparative Example 3:
[0127] The vacuum condition in the process of preparing the positive electrode and negative electrode slurries was removed, and the preparation was carried out under normal room pressure. Other conditions were the same as in Example 1.
[0128] Comparative Example 4:
[0129] The stepwise addition in the total mixing step during the preparation of the positive and negative electrode slurries was changed to a one-time addition, and the other conditions were the same as in Example 1.
[0130] Observation of the surface morphology of the pole piece:
[0131] The positive electrode sheets and negative electrode sheets prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were photographed using a scanning electron microscope (SEM) to observe the surface micromorphology of the samples. Figure 1 is a surface morphology diagram of the positive electrode sheet of Example 1 of the present application, Figure 2 is a surface morphology diagram of the negative electrode sheet of Example 1 of the present application, Figure 3 is a surface morphology diagram of the positive electrode sheet of Comparative Example 1 of the present application, Figure 4 is a surface morphology diagram of the negative electrode sheet of Comparative Example 1 of the present application, Figure 5 This is a surface morphology of the positive electrode sheet of Comparative Example 2 of the present application, Figure 6is a surface morphology diagram of the negative electrode sheet of Comparative Example 2 of the present application, Figure 7 is a surface morphology diagram of the positive electrode sheet of Comparative Example 3 of the present application, Figure 8 is a surface morphology diagram of the negative electrode sheet of Comparative Example 3 of the present application, Fig. 9 is a surface morphology diagram of the positive electrode sheet of Comparative Example 4 of the present application, Fig.10 The surface morphology of the negative electrode sheet of the comparative example 4 of the present application is shown in FIG. The surface morphology of the electrode sheets of the embodiment and the comparative example is observed using a scanning electron microscope. Figures 1 to 10 The coatings of the positive and negative electrodes of Example 1 are uniformly dispersed and have no agglomeration phenomenon; the coatings of the positive and negative electrodes of Comparative Example 1 are uniformly dispersed and have no agglomeration phenomenon ( Figures 1 to 10 The electron microscopic morphology of the image is a picture of the dry electrode before the electrolyte is added, so the effect of the electrolyte on the electrode cannot be seen. When the battery is subsequently tested for performance, the electrolyte composition in the battery of Comparative Example 1 is different, and the battery of Comparative Example 1 did not pass the test); after the positive electrode in Comparative Example 2 is removed from the ultrasonic process, the positive electrode material is obviously agglomerated and unevenly dispersed; after the positive electrode in Comparative Example 3 is removed from the vacuum, there are many pits on the surface of the electrode (the reason is that the gas inside the slurry cannot be removed in time, and it remains on the surface of the electrode after coating), and pitting can be seen on the negative electrode. In Comparative Example 4, step-by-step feeding is not used, and the uniformity of the primary particles in the positive electrode material to the secondary particles is poor, and there are pitting on the surface of the positive and negative electrodes.
[0132] It should be noted that pitting refers to many small uneven point defects formed on the surface of the electrode sheet. Pitting will cause the electrode surface to be uneven, affecting the uniformity and conductivity of the electrode, thereby reducing the performance of the battery, such as capacity, rate performance and cycle life.
[0133] Performance Test:
[0134] 1) Peeling force test: Use an electronic tensile testing machine to test the peeling of the material on the surface of the pole piece at a speed of 250 mm / min, a test time of 36.2 s, and a maximum deformation of 150 mm.
[0135] 2) Internal resistance test: Use a lithium-ion battery internal resistance tester to test the battery internal resistance.
[0136] 3) Battery AC internal resistance (DCR) detection: Use the Nebula lithium-ion battery test cabinet to charge the battery to 100% SOC, then discharge it to 50% SOC and let it stand for 1 hour. Then discharge it at 1C for 30S and calculate the battery AC internal resistance.
[0137] 4) Overcharge and over-discharge test: According to the national standard GB31241-2022, if the battery is charged to 6.3V at 1C and does not catch fire or explode, it has passed the overcharge test. If the battery is discharged to 2V at 1C and does not catch fire or explode, it has passed the over-discharge test. If the battery catches fire or explodes, it has failed the overcharge and over-discharge test.
[0138] 5) Hot box test: When fully charged, heat the battery to 135°C and keep it warm for 1 hour. If the battery does not catch fire or explode, it passes the hot box test. If the battery catches fire or explodes, it fails the hot box test.
[0139] 6) Thermal runaway test: A fully charged battery is heated until it catches fire and explodes. If the battery can open the valve in a certain direction, it has passed the thermal runaway test. If the battery explodes and the valve does not open in a certain direction to release pressure, it has failed the test.
[0140] The test results are shown in the table below:
[0141]
[0142] In this application, in Comparative Example 1, LiSFI in the electrolyte is removed, and the battery generates heat until it explodes during the hot box test, and cannot pass the hot box test. In Comparative Example 2, the positive and negative electrode materials are ultrasonically removed during preparation, and the internal resistance of the battery is high, the adhesion of the pole pieces is poor, and it cannot pass the overcharge and over-discharge test. In Comparative Example 3, the positive and negative electrode materials are vacuum removed during preparation, and the internal resistance of the battery is high, the adhesion of the pole pieces is poor, and it cannot pass the thermal runaway test. In Comparative Example 4, the total mixing is not performed in steps, the internal resistance of the battery is high, the adhesion of the pole pieces is poor, and it cannot pass the overcharge and over-discharge test and the thermal runaway test.
[0143] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.
Claims
1. A method for preparing a positive electrode slurry or a negative electrode slurry, wherein the raw materials of the positive electrode slurry include a positive electrode active material, a conductive agent, a binder and a solvent, and the raw materials of the negative electrode slurry include a negative electrode active material, a conductive agent, a binder and a solvent, and the raw materials of the positive electrode slurry and the raw materials of the negative electrode slurry include liquid raw materials and solid raw materials, characterized in that: The preparation method comprises: Preparing a first mixed material: mixing the binder and the liquid raw material to obtain the first mixed material; Preparing a second mixed material: mixing the solid raw materials to obtain the second mixed material; Preparing a third mixed material: adding the first mixed material to the second mixed material, and mixing them evenly to obtain the third mixed material, that is, the positive electrode slurry or the negative electrode slurry; in: At least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material is performed in a vacuum environment; In at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material, mixing is performed by ultrasonic treatment.
2. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum environment is -5MPa to -1MPa.
3. The preparation method according to claim 1 or 2, characterized in that: The frequency of the ultrasound is 10kHz to 20kHz.
4. The preparation method according to claim 3, characterized in that: In at least one of the steps of preparing the first mixed material, preparing the second mixed material, and preparing the third mixed material, mixing is also performed by stirring, the stirring rate is 2000rpm to 4000rpm, and the processing time is 0.5h to 3h.
5. The preparation method according to claim 1, characterized in that: In the step of preparing the third mixed material, the first mixed material is added to the second mixed material in multiple times.
6. A positive electrode slurry or a negative electrode slurry prepared by the preparation method according to any one of claims 1 to 5.
7. A positive electrode material or a negative electrode material, characterized in that: The positive electrode material comprises the positive electrode slurry according to claim 6 , and the negative electrode material comprises the negative electrode slurry according to claim 6 .
8. A battery, characterized in that: The battery comprises: the positive electrode material as claimed in claim 7, the negative electrode material as claimed in claim 7, and an electrolyte.
9. The battery according to claim 8, characterized in that The electrolyte includes LiFSi in an amount of 0.1% to 20%.
10. A method for preparing a battery as claimed in claim 8 or 9, characterized in that: include: Preparing positive electrode materials and negative electrode materials: including preparing positive electrode slurry and negative electrode slurry, and coating to obtain the positive electrode material and the negative electrode material; Preparing an electrolyte: the electrolyte comprises a lithium salt, a solvent and an additive; The positive electrode material and the negative electrode material are assembled and injected with the electrolyte to obtain the battery.
Citation Information
Patent Citations
Preparation method of positive electrode slurry
CN109888288A
Preparation method of multi-element positive pole piece
CN117334844A
Preparation method of battery positive electrode slurry
CN118693235A
Manufacturing method for battery electrode
JP2017010797A
Cathode and cathode slurry for secondary battery
US20230073006A1